Bank Specific Factors and Their Impact on Bank Deposits: A Study of Nepalese Commercial Banks - Dongol, Rosy (Apex Journal of Business and Management, 2024)
This study investigates the impact of bank-specific factors on the deposits of Nepalese commercial banks. Bank deposits are crucial financial arrangements where customers entrust their funds to banks, which utilize these deposits to generate revenue through loans and financial services. The research employs secondary data analysis, utilizing data from 20 commercial banks over a five-year period (2075-2079) with 100 observations. Descriptive statistics, trend analysis, and regression analysis were conducted to assess the relationships between the dependent variable (deposits) and independent variables (capital, profitability, non-performing loans, number of branches, interest rates, and liquidity).The findings reveal that paid-up capital, the number of branches, and saving interest rates positively and significantly impact deposits, while non-performing loans negatively affect deposits. Conversely, profitability (ROA and ROE), liquidity (current and quick ratios), and fixed deposit interest rates do not significantly influence deposits. These results underscore the importance of capital, branch accessibility, and competitive interest rates in enhancing deposit mobilization. The study concludes that banks should develop strategies to leverage positive factors and mitigate negative influences to foster deposit growth, thereby supporting economic stability and growth in Nepal.